The Relationship Between Economic Development and Selected Economic Indicators of the United States of America (European Journal of Economics, Finance and Business Development, 2023)
Purpose: The United States is a highly developed mixed economy. It is the world's largest economy by nominal GDP. Indeed, in some research it is been shown that there are a lot of factors that effect on the development of the US economy and one the most important of them is GDP (Gross Domestic Product) per capita. The major goal of this study is to identify the challenges that the US will encounter and how they will affect the growth of the US economy over the next five years. Secondary data from secondary sources were retrieved for the current investigation such as an independent variable and a dependent variable used in this study, the data were prepared from the Federal Reserve Economic data (FRED), from 1980 to 2021. In our research used annual time-series data and the OLS model on GDP per capita was the dependent variable, while Inflation, Unemployment, Exchange rate, FDI, Interest rate and Export were the independent variables. Using multi-factor time-series models, particularly VAR model analysis, we analyzed that GDP per capita has been found to have positive and negative relationships with, FDI, Interest rate, Export, Import, Industry, Unemployment rate. Moreover, after using forecast test, we predicted that in the next 5 years the Economy of USA will face some fluctuations and increase, so that reason government should consider all the factors that affect the development of the state economy.